Cardiosphere-derived cells in the primary prevention of sepsis-induced acute lung injury in pigs - James Frederick Dawkins; Asma Nawaz; Lizbeth Sanchez; Ralf Sulague; Aiyana Verfaillie; Juan Cardenas; Eugenio Cingolani; Michael Lewis; Eduardo Marban (PLoS ONE, 2026)
Acute respiratory distress syndrome (ARDS) prevention in patients coincide with significant risk factors, including severe sepsis. Cardiosphere-derived cells (CDCs) are cardiac stromal/progenitor cells with anti-inflammatory and immunomodulatory effects, which may impact favorably on sepsis-induced acute lung injury (ALI). We used a pig model of sepsis (lipopolysaccharide, LPS) to test whether CDCs, given IV in a preventive paradigm, can ameliorate ALI, relative to placebo. Yorkshire/Landrace hybrid domestic pigs (n = 34) were divided into 3 groups: 1) healthy controls; 2) LPS (60ug/kg) + saline (placebo) group; and 3) LPS + CDC group, with CDCs given in 3 different doses (25, 50 and 100 million cells) after LPS. All pigs were briefly intubated on mechanical ventilation on room air to obtain baseline and 1-hour data and again at the final endpoint of 48hours. Chest mechanics, gas exchange, hemodynamics, blood, bronchoalveolar lavage assays and lung histology were assessed. LPS + CDCs compared with LPS + saline improved: gas exchange (increased hypoxemia ratio [p = 0.03],chest mechanics (respiratory compliance [p = 0.002]; peak and plateau pressures [p = 0.01/0.049]), pulmonary hemodynamics (decreased pulmonary artery pressures [p = .0008]), reduced BAL neutrophils [p = 0.04]), and systemic cytokines, e.g., IL-1, IL-6, IL-18 and IFNγ [p < 0.05]) and serum creatinine (p = 0.02), while alveolar lavage cytokines, e.g., IL-1, IL-6,IL-8,and IL-18 were changed. Histopathology was improved (decreased atelectasis, hemorrhage and arteriolar thickness). In summary, CDCs given in a preventive fashion, attenuated manifestations of LPS-induced ALI. As CDCs have an extensive safety record in hundreds of patients, our findings motivate clinical testing of CDCs for the primary prevention of sepsis-induced ARDS.